The Determinants of Intellectual Capital Disclosure Among Malaysian Listed Companies - Siti Mariana, Taliyang @ Alias (2010)
The purpose of this study is to examine the extent of the intellectual capital (IC) disclosure by Malaysian listed companies. The study aims to investigate whether the following variables determine the IC disclosure by Malaysian listed companies. The variables tested in this study are; ( 1 ) age; (2) size: (3) leverage: (4) profit; (5) ownership; and (6) growth. A sample of 150 companies listed on Bursa Malaysia was selected consisting of five industries which are; Information Technology. Consumer Product, Industrial Product. Trading/Services and Finance. The content analysis, descriptive analysis and ordinary lease squares (OLS) regression model are performed in this study. The total IC disclosed by the companies is measured using a modified model popularized by Bontis (2003) and Vergauwen and van Alem (2005). The results reveal the extent of the intellectual capital disclosure among Malaysian companies is still relatively low. However. the study reveals that, there is high intellectual capital disclosure among Malaysian listed companies as indicated at 72.6 percent. Besides that, out of six variables being tested, only three variables can be concluded as a determinant of intellectual capital among Malaysian companies. They are size, growth and director ownership.